GELATINASE ACTIVITY OF METABOLITES OF PSEUDOMONAS FLUORESCENS MIGULA ON LARVAE AND PUPAE OF CULEX QUINQUEFASCIATUS (DIPTERA: CULICIDAE) - USHARANI BRAMMACHARRY; KUMMANKOTTIL PAILY (International Journal of Pharma and Bio Sciences, 2014)
To determine the effect of gelatinase activity of mosquitocidal protein of P. fluorescens Migula strain (VCRC-B426) on larvae and pupae of Culex quinquefasciatus was studied. The results of Enzchek Gelatinase/Collagenase assay revealed that the mosquitocidal metabolite exhibited the gelatinase/collagenase activity and efficiently digested the fluorescein conjugate-DQ gelatin to yield highly fluorescent peptides. The arbitrary units of fluorescence emission at various concentration of substrate and various concentration of enzyme are measured. The increases in fluorescence are proportional to proteolytic activity and can be monitored with SYBER green end point assay. The Vmax and Km of Michaelis-Menten equation analysis of kinetics assay of the gelatinase activity of protein (mg/ml) at 95% confidence intervals are 18.01 and 3.335 respectively. The gelatinase activity of mosquitocidal protein was studied with increasing the DQ gelatin concentration. The Vmax and Km of Michaelis-Menten equation analysis of gelatinase assay of different concentration of DQ gelatin substrate (ug/ml) at 95% confidence intervals are 15.82 and 4.907 respectively. In this study, the gelatinase activity of mosquitocidal protein of P. fluorescens is likely to play important roles in the degradation of abendunt gelatine molecule in cuticular regions and peritrophic membrane of larvae and pupae of Cx.quinquefasciatus.